Data Visualization in Society 2020
DOI: 10.1515/9789048543137-024
|View full text |Cite
|
Sign up to set email alerts
|

20. What a line can say : Investigating the semiotic potential of the connecting line in data visualizations

Abstract: The line is a graphical element widely used in data visualizations, its purpose often being to signal a connection between other visual elements. Based on social semiotic theory, this article investigates what semiotic functions connecting lines can have and how these functions can be related to variations in form. The results show that, in addition to the basic function of connecting elements, such lines can also indicate the level of certainty, direct the viewer to read the information either as a narrative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Previous research has shown that diagrams regularly use arrows and lines for diverse communicative functions: they can, for example, represent processes and relationships that hold between diagram elements (see e.g. Alikhani and Stone, 2018;Lechner, 2020b). Lechner (2020a, p. 118), who explores how data visualizations use connecting lines to express uncertainty, observes that the iconic qualities of arrows and lines can determine or complement their communicative functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown that diagrams regularly use arrows and lines for diverse communicative functions: they can, for example, represent processes and relationships that hold between diagram elements (see e.g. Alikhani and Stone, 2018;Lechner, 2020b). Lechner (2020a, p. 118), who explores how data visualizations use connecting lines to express uncertainty, observes that the iconic qualities of arrows and lines can determine or complement their communicative functions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that cut-out diagrams are characterized by relatively stable layout patterns in which the depicted object is placed in the center of the layout, whereas the parts of the object are picked out using lines and written labels (Hiippala and Bateman, 2022b;Hiippala, 2023). Given that cutout diagrams use lines to represent part-whole structures, it may be assumed that they would prefer to use thinner arrows and lines than cycles, which use these elements to represent processes and other phenomena (Lechner, 2020b). However, conducting a hybrid search for arrows among cut-out diagrams by using the same element as in Figure 6 returns mixed results, which are shown in Figure 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation